A Peircean semiotic analysis of international poster design: Study of Petra Christian University and Sophia University - Karina Anggi Dabi-Dabi; Listia Natadjaja; Bernadette Dian Arini Maer (Asosiasi Program Studi Desain Komunikasi Visual Indonesia (Asprodi DKV), 2025)
Posters are a form of visual communication that conveys information to the audience. This study analyzes the design of each three international activity posters from Petra Christian University (Indonesia) and Sophia University (Japan) using Peirce's semiotic theory, by dividing signs into icons, indices, and symbols to reveal the meaning of the visual components used. The visual components (signs) observed consisted of dots, lines, shapes, colors, textures, spaces, images, illustrations, typography, and layouts found in each poster. The results of the analysis show that Petra Christian University displays diverse visual components and global collaboration, while Sophia University reflects Japanese culture and local identity. Through the points of difference and similarity that have been explained, Petra Christian University and Sophia University demonstrate consistency in their designs and have very different design characteristics. This research provides insight into how meaning is formed in poster design through a semiotic approach, as well as the importance of understanding the cultural context in visual communication between countries.